Polylactic acid and polyhydroxybutyrate coating on hemp fiber: Its effect on hemp fiber reinforced epoxy composites performance - Behera S.; Gautam R.K.; Mohan S. (My University, 2025)
The present research work investigated the influence of biodegradable polymer coatings of hemp fiber on the structural, water absorption, mechanical, and tribological properties of hemp fiber and hemp fiber reinforced epoxy composites (HFREC). Hemp fibers were initially treated with sodium hydrogen carbonate and then coated with biodegradable polymers like polyhydroxybutyrate (PHB) and polylactic acid (PLA). Scanning electron microscopy (SEM) images of the coated fibers showed a visible change in fiber surface and improvement in surface roughness, while; X-Ray diffraction (XRD) analysis indicated the improvement in crystallinity of the coated fibers resulting in enhanced interfacial adhesion between the coated fibers and the epoxy matrix. The experimental results also revealed that both PHB and PLA coatings of the fibers have resulted in improvement of water resistance and mechanical properties such as tensile strength, modulus, and impact strength of coated HFREC. Tribological test results also revealed that the coated HFREC have improved wear and frictional properties in comparison to uncoated HFREC. The best tribological and mechanical properties were exhibited by PLA coated HFREC, which was also confirmed through the SEM images of worn and fractured surfaces of the uncoated and coated hemp fiber composites. © The Author(s) 2022.